Evaluating freshwater lens morphology affected by seawater intrusion using chemistry-resistivity integrated technique: a case study of two different land covers in Carey Island, Malaysia - Tajul Baharuddin, M. F.; Othman, A. R.; Taib, S.; Hashim, R.; Zainal Abidin, M. H.; Radzuan, M. A. (2013)
Freshwater lenses are vital to small island communities but are susceptible to seawater intrusion due to the physical changes in the shoreline land cover. The effect of seawater intrusion and irrigation water on a coastal unconfined aquifer beneath naturally preserved mangrove and deforested mangrove-barren belt was investigated in Carey Island. Analysis of the total dissolved solids (TDS) and earth resistivity (ER) using a geochemistry-electrical integrated technique gave a TDS–ER relationship capable of predicting freshwater lens morphology affected by sea-irrigation water. The study result shows freshwater was fourfold thicker in close proximity of the mangrove forest than the mangrove barren area; the further the shoreline from the mangrove thickest section, the less vulnerable was the seawater intrusion and the more fresh the irrigation water, and hence the greater the freshwater availability potential.